Methodology for Evaluating Applicability of Real Estate Information Systems - Klimach, Anna (Geomatics and Environmental Engineering, 2025)
This article proposes a methodology for evaluating the applicability of real estate information systems. Despite the fact that such systems have been created by different agencies and for different reasons, all of them should effectively deliver their designed functionalities. These functionalities are determined by the types of users. Real estate information systems have been developed on the assumption that they would be accessible to all citizens; therefore, the applicability of these systems should be examined. In this context, applicability is defined as the degree to which a product, system, or service enables users to achieve their goals in an efficient, effective, and satisfactory manner. A universal methodology for evaluating the applicability of a given system has been proposed and validated in this study. Certain limitations of real estate information systems that could affect their use in land administration procedures were also identified.